PENGARUH ALOKASI ANGGARAN PENDAPATAN DAN BELANJA DAERAH TERHADAP PENANGANAN STUNTING PADA KABUPATEN/KOTA DI DARATAN TIMOR PROVINSI NUSA TENGGARA TIMUR - Mansula, Renanta Linggar; Demu, Yohanes; Muga, Maria Prudensiana Leda (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2024)
This study aims to determine the effect of the Regional Revenue and Expenditure Budget Allocation on handling stunting in Districts / Cities in the Timor Mainland of East Nusa Tenggara Province. Quantitative research using statistical analysis is the methodology employed. This research used multiple linear regression testing, hypothesis testing, classical assumption testing, validity and reliability testing, and descriptive statistical testing as analytical methodologies. The research included a sample of 45 public health department personnel from five districts/cities in Timor Mainland, East Nusa Tenggara Province. The results showed: (1) Regional Original Revenue does not impact the effective management of stunting. (2) The impact of the Special Allocation Fund on the management of stunting, (3) Village Fund has no effect on handling stunting, (4) The management of stunting is impacted by other legitimate regional revenues. (5) Regional Original Revenue, Special Allocation Fund, Village Fund, and More legitimate regional revenues impact the management of stunting.